Purified lymphocyte function-associated antigen-3 and T11 target structure are active in CD2-mediated T cell stimulation. - Tiefenthaler, G; Hünig, T; Dustin, M; Springer, T; Meuer, S (1987)
In this study we have used cells expressing LFA-3 or T11TS, the human and sheep forms of the ligand of CD2, as well as the purified LFA-3 and T11TS molecules themselves to study their effects on T cell activation via the CD2-mediated "alternative pathway". Sheep red blood cells, which bind to CD2 via T11TS in E-rosette formation, and human autologous monocytes, which express the LFA-3 molecule, both induce proliferation of resting T cells in the presence of per se submitogenic concentrations of anti-T11(2) plus anti-T11(3) monoclonal antibodies (mAb). This effect is blocked by mAb to LFA-3, T11TS and CD2 known to inhibit CD2-ligand interaction. In addition, purified LFA-3 and T11TS, when added at ng amounts to cultures containing submitogenic concentrations of anti-T11(2 + 3) mAb, are also strongly mitogenic for resting human T cells. Thus, both LFA-3 and T11TS are potent co-stimulators of the alternative pathway of T cell activation but by themselves do not provide a mitogenic signal. This finding is discussed with regard to a physiological role of CD2-LFA-3 interaction in T cell activation.